2018
DOI: 10.1038/s41598-018-19742-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the osteogenesis and osseointegration of titanium alloys coated with graphene: an in vivo study

Abstract: The aim of this study was to investigate whether a surface coating with graphene could enhance the surface bioactivation of titanium alloys (Ti6Al4V) to further accelerate in vivo osteogenesis and osseointegration at the implant surface. In this study, a New Zealand white rabbit femoral condyle defect model was established. After 4, 12 and 24 weeks, biomechanical testing, micro-computed tomography (Micro-CT) analyses and histological observations were performed. At the highest push-out forces during the test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 51 publications
1
42
1
Order By: Relevance
“…21,22 On the basis of GO, it is possible for carboxyl, 23 amino, 24 hydroxyl 25 and other functional groups to be introduced not only to improve the fluidity and dispersion of graphene, but also to further endow it with new functions, among which is that various active substances can be loaded to improve bioactivities. 26,27 At present, the functionalized GDs have been compounded with various substrates such as metals, 28 inorganic, 29 natural polymer 30 and synthetic polymer 31 to prepare scaffolds, 32,33 coatings, 34 membranes 35 and injectable hydrogels. 36 Lots of studies in vitro and in vivo have demonstrated that the GDscontaining composites could regulate the extracellular microenvironment to effectively promote bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 On the basis of GO, it is possible for carboxyl, 23 amino, 24 hydroxyl 25 and other functional groups to be introduced not only to improve the fluidity and dispersion of graphene, but also to further endow it with new functions, among which is that various active substances can be loaded to improve bioactivities. 26,27 At present, the functionalized GDs have been compounded with various substrates such as metals, 28 inorganic, 29 natural polymer 30 and synthetic polymer 31 to prepare scaffolds, 32,33 coatings, 34 membranes 35 and injectable hydrogels. 36 Lots of studies in vitro and in vivo have demonstrated that the GDscontaining composites could regulate the extracellular microenvironment to effectively promote bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Osteolysis evaluated by X-ray was not observed in both the smooth and DED groups, but micro-CT analysis is necessary to make an accurate evaluation [36]. However, due to the metal interference effect of CoCr alloy and titanium, an accurate image of the bone-implant contact surface could not be obtained.…”
Section: Discussionmentioning
confidence: 96%
“…This may result from better adhesion strength between graphene-coatings and Ti substrates, which helped to maintain the integrity of graphene-coatings even under sustained mechanical interferences from in vivo environment. Clearly, this conclusion is limited to the animal models employed in our study, and graphene-coated titanium bone implants and in situ osteointegration 62 will be a practical in vivo model to illustrate the future application of graphene-coated Ti implants. Basing on the methods to enhance and evaluate the adhesion strength of graphene-coatings on Ti as proposed in this study, we will uncover the exact effect of bone integration of graphene-coated titanium bone implants in vivo by using the in situ osteointegration model in our future experiments.…”
Section: Discussionmentioning
confidence: 99%